The Effect of Health Counseling on Mother's Knowledge About Stimulation of Development of Toddlers Aged 3-5 Years in Jati Mulya Perbaungan Village in 2021 - Purnama Handayani; Rizki Noviyanti Harahap (Science Midwifery, 2022)
Developmental stimulation is needed by children. The delay in child development can also be caused by the lack of stimulation received by the child, both by caregivers and parents, the purpose of this study was to determine whether to determine the Effect of Health Counseling on Mother's Knowledge About Stimulation of Development of Toddlers Aged 3-5 Years in the Village Jati Mulya Perbaungan in 2021. This study uses this type of research. The population in this study are all mothers who have toddlers aged 3 to 5 years in Jati Mulyo Village, Dusun 3, Pegajahan District, Serdang Bedagai Regency. Data analysis used Wilcoxon test 95%. The results of this study showed that there was an effect of health counseling on mother's knowledge about stimulation of the development of toddlers aged 3-5 years in Jati Mulya Perbaungan Village in 2021, with a p value (0.000) < (0.05). The conclusion is that it can be concluded that these results prove that health counseling can have a positive influence on increasing mother's knowledge about stimulating the development of toddlers aged 3-5 years in Jati Mulya Perbaungan Village in 2021. It is recommended that health workers can increase public knowledge by holding counseling once a month about stimulating the development of children aged 3-5 years using the lecture, discussion and demonstration method with leaflets and stimulation tools or children's toys